Geografias animais: perspectivas anglo-saxãs, francesas e brasileiras - Guillaume Marchand; Farid Benhammou; Fabio Coltro (Confins)
Over the past 25 years, human geography has undergone a process of diversification in order to integrate new objects of study within its field of reflection, which includes animals. The objective of this paper is to introduce the principles of animal geography to the Brazilian academic public to whom they remain unknown. In this context, we will proceed with a retrospective on the evolution of both Anglo-Saxon and French animal geographies revealing their convergent and divergent points. We decided to restrict to these two poles of academic production since both generally provide Brazilian geographers with the major sources of bibliographical reference for matters of emerging research. Finally, we will carry out a few reflections on the conditions of animal geography growth in Brazil as well as its potential in terms of contribution to the decolonization of animal geography.